A study of supply chain management: a case study of Celestica Electronic / Maisarah Mohamed - Mohamed, Maisarah (Faculty of Business and Management, 2010)
Celestica Inc. is a multinational electronics manufacturing services (EMS) company headquartered in Toronto, Canada. Celestica operates a global manufacturing network with operations in Asia, Europe and the Americas, providing a broad range of integrated services and solutions to leading OEMs (original equipment manufacturers). Celestica was incorporated as a wholly owned subsidiary of IBM in January 1994. Onex Corporation acquired Celestica in October 1996 and controls approximately 69% of the company's voting shares. Celestica’s global manufacturing network comprises more than 40 locations in the Americas, Europe and Asia. The company's global services include design and engineering, manufacturing and systems assembly, fulfillment and after-market services. This Celestica site in Malaysia is located in the Tampoi Industrial Estate, in Johor Bahru. This facility specialized in Printed Circuit Board Assembly, Repair services, Systems Assembly and Test. One of the earliest established industrial areas in Johor Bahru, this site is a short 30 minutes drive to Singapore and a 35 minutes flight from Kuala Lumpur. Celestica’s Johor Bahru facility has the most comprehensive PCA offering in Asia, with focus on the industrial and enterprise market segments. The team is highly competent in both low mix high volume and high mix-low volume System Assembly and Printed Circuit Board Assembly and experienced in RF. Its close proximity to Singapore allows products to be shipped globally through Singapore’s superior logistics infrastructure